O18.3 Adolescents in south africa and assessment of hiv risk: knowing who we are trying to protect. (13th September 2015) - Barnabas, S; Dabee, S; Jaspan, HB; Jaumdally, SZ; Gamieldien, H; Masson, L; Lewis, D; Wallace, M; Bennie, T; Gray, C; Williamson, AL; Hope, T; et al.
Abstract : Introduction: South African adolescent females are at high risk of HIV acquisition, disproportionate to their sexual behaviour. We hypothesised that biological changes associated with puberty may influence this susceptibility. Methods: This study was conducted in two South African sites, the Desmond Tutu Youth Centre, Masiphumele, Cape Town and the Perinatal HIV Research Centre, Soweto, Johannesburg. Cytokines were measured by Luminex. Sexual risk behaviour, contraceptive use and the prevalence of sexually transmitted infections (STIs) [ C. trachomatis (CT), N. gonorrhoeae (NG), T. vaginalis, M. genitalium, HSV-2, syphilis], bacterial vaginosis (BV) and candida were assessed in each women. Results: The prevalence of STIs or BV was 71% in Cape Town and 54% in Johannesburg, with 47% of Cape Town and 42% of Johannesburg women having BV. The CT prevalence in Cape Town [62/148 (42%)] was substantially higher than Johannesburg [26/149 (17%); p < 0.0001]. CT was highest in 16–17 year old women and lowest in 20–22 year olds in both sites. Among the Cape Town CT isolates studied in detail (n = 40/62), five distinct sequence types were seen. Despite these differences in STI/BV prevalence between cohorts, the women had largely similar behavioural risk profiles, including sexual orientation, age of sexual debut and lifetime number of sexual partners, though adolescents from Johannesburg were more likely to report previous known symptomatic STIs (p = 0.03). BV was the most inflammatory condition, with upregulated concentrations of many of cytokines and growth factors observed in both sites. While CT was associated with more moderate cytokine up-regulation in Cape Town, high levels of inflammation were observed in CT positive women from Johannesburg. Conclusion: An alarmingly high STI and BV prevalence was found in these at risk populations, indicating a need for improved preventative strategies. In young women, BV caused a greater degree of inflammation than STIs and its effective management requires further investigation. This work was supported by a Strategic Health Innovation Partnerships (SHIP) grant from the South African Medical Research Council and European and Developing Countries Clinical Trials Partnership (EDCTP). The cohort was supported by grants from the EDCTP. SLB was supported by the HIV Vaccine Trials Network, the Fogarty Foundation and the South African Medical Research Council (MRC). No pharmaceutical grants were received in the development of this study.